Mewujudkan Model Desa yang Ramah Perempuan dan Peduli Anak sebagai Upaya Mencegah Pekerja Anak di Sektor Pertanian - laily mufid, firda (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2022)
The challenge facing Indonesia today is child labor in the agricultural sector. Agricultural land which is the center of livelihood for most of Indonesia's population makes children as workers in the agricultural sector. Based on data on the assessment of child labor in Indonesia in the agricultural sector and recommendations by Modelez International in 2020, there are more than 4 million child workers in Indonesia and 20.7 percent of them are trapped in hazardous work environments or the Worst Forms of Child Labor (WFCL). Strategies to reduce the number of child labourers. among others, ensuring that the issue of child labor remains in the policies and programs of special child protection in the district or city. Development of a women-friendly and child-friendly village model as an approach to child labor prevention and coordination of child labor prevention in 4 priority sectors, namely agriculture, fisheries, services, and tourism. The purpose of this paper is to find out the legal protection of child labor in the agricultural sector, especially in Indonesia and to explain the realization of the women-friendly and child-friendly village model. The result of this paper is the realization of a women-friendly and child-friendly village model that can be used as a model for other villages in Jember district. The recommendation to be achieved is the existence of a village pilot area that is friendly to women and cares about children which can be directly fostered by the relevant agencies.